where , and are positive integers and and are coprime. What is ?
is the Reimann Zeta Function
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I = ∫ 0 π / 2 tan ( x ) ln ( cos ( x ) ) ln ( sin ( x ) ) d x
I = ∫ 0 π / 2 sin ( x ) ln ( cos ( x ) ) ln ( sin ( x ) ) cos ( x ) d x
Make u = sin ( x ) . Then, cos ( x ) d x = d u and cos ( x ) = 1 − u 2 = ( 1 − u 2 ) 2 1 (the positive square root, since x ∈ ( 0 , π / 2 ) ):
I = ∫ 0 1 u ln ( ( 1 − u 2 ) 2 1 ) ln ( u ) d x
I = 2 1 ∫ 0 1 u ln ( 1 − u 2 ) ln ( u ) d x
Then, by integration by parts making f = ln ( 1 − u 2 ) and g ′ = u ln ( u ) :
I = 2 1 ⎣ ⎡ 2 ln ( 1 − u 2 ) ln 2 ( u ) ∣ ∣ ∣ ∣ ∣ 0 1 + ∫ 0 1 1 − u 2 u ln 2 ( u ) d u ⎦ ⎤
The first term goes to 0 both when u → 0 and when u → 1 . This can be shown by the series of ln ( 1 − x ) for ∣ x ∣ < 1 (see below). Thus:
I = 2 1 ∫ 0 1 1 − u 2 u ln 2 ( u ) d u
We then make u = e t . Then d u = e t d t and:
I = 2 1 ∫ − ∞ 0 1 − e 2 t e t t 2 e t d t
Multiplying above and below by e − 2 t :
I = 2 1 ∫ − ∞ 0 e − 2 t − 1 t 2 d t ;
Now we make t = − 2 v , d t = − 2 d v
I = 1 6 1 ∫ 0 ∞ e v − 1 v 2 d v
By the definition of the Riemann zeta function ζ ( s ) :
ζ ( s ) = Γ ( s ) 1 ∫ 0 ∞ e x − 1 x s − 1 d x
This integral will be exactly equal to:
I = 1 6 1 Γ ( 3 ) ζ ( 3 )
Where Γ ( z ) is the Gamma function . Since Γ ( z ) = ( z − 1 ) ! :
I = 8 1 ζ ( 3 ) a = 1 , b = 8 , c = 3 → a + b + c = 1 2
NOTE: The aforementioned proof. Consider:
C = ln ( 1 − u 2 ) ln 2 ( u )
By the Taylor series of ln ( 1 − x ) :
C = − k = 1 ∑ ∞ k ln 2 ( u ) u 2 k
When u = 1 , ln ( u ) = 0 and C = 0 .
When u = 0 :
C = − k = 1 ∑ ∞ u → 0 lim u 2 k k ln 2 ( u )
In each term of the sum, we'll have a ∞ / ∞ case, in which L'Hôpital's rule applies:
C = − k = 1 ∑ ∞ u → 0 lim u 2 k + 1 − 2 k 2 u 2 ln ( u )
C = k = 1 ∑ ∞ u → 0 lim u 2 k k 2 ln ( u )
Again a ∞ / ∞ case, in which L'Hôpital's rule applies:
C = k = 1 ∑ ∞ u → 0 lim u 2 k + 1 − 2 k 3 u 1 .
C = k = 1 ∑ ∞ u → 0 lim 2 k 3 − u 2 k .
Which will also make C = 0 as u → 0